Friday

April 18, 2014

April 18, 2014

Posted by **Lena** on Tuesday, February 24, 2009 at 8:11pm.

y=-3x^2 + 4x

This is how I solved it:

y=-3x^2 + 4x

y= -3 (x^2 + 4/3x)

y= -3(x^2+4/3x +4/9) + 4/3

y= -3 (x+2/3)^2 + 4/3

The answer sheet said that x = 2/3 but wouldn't it equal -2/3 because there is a -3 before the bracket?

- Find the minimum/maximum -
**bobpursley**, Tuesday, February 24, 2009 at 8:23pmy=-3x^2 + 4x

y= -3 (x^2 + 4/3x)You erred here, it should be

y=-3x^2 + 4x

y= -3 (x^2 - 4/3x )

- Find the minimum/maximum -
**Lena**, Tuesday, February 24, 2009 at 8:28pmoh ok

thanks so much :)

**Related Questions**

calc - 6(4x+3)^5(4)(3x-5)^5+ 5(3x-5)^4(3)(4X+3)^6 common factors: (4x+3)^5 (3x-5...

bobpursley,math - about this problem , I figured it out and i did get the answer...

Algebra2 - Complete parts a – c for each quadratic function: a. Find the y-...

math,bobpursly, - 4x-2x^2+4x^3 from 4x^3+x-3x^2 4x^3+x-3x^2 -( 4x-2x^2+4x^3) ...

mathh - Let f(x)=x+2 Ix-3I and g(x)=3x-1 Find all solutions to the equation f(g(...

math - sums and differences of rational algebraic expression please answer the ...

Math - Can someone please check my answers below for accurateness? The ...

Algebra - (3x+4)/(3x-4)+(3x-4)/(3x+4) --------------------------- Divide top by ...

algebra - thank everyone that site helped but now i just have to practice. for ...

Math - Can you check these questions for me? 1. Add: (3x^4-x+2)+(9x^5-x^2+x) 9x^...